POTENTIALS AND STRATEGIES OF INDONESIAN FRUIT EXPORTS TO THE UNITED ARAB EMIRATES - Elpawati; Zulmaneri; Fajar Widyaharsanto (Syarif Hidayatullah State Islamic University Jakarta, 2026)
Indonesia has significant potential in tropical fruit production; however, its export performance in non-traditional markets, especially to the United Arab Emirates (UAE), remains suboptimal. This study analyzes the potential and development strategies for Indonesian fruit exports to the UAE by examining competitiveness, trade dynamics, and key economic determinants. The research utilizes secondary data from 2019 to 2024 obtained from the Central Statistics Agency / Statistics Indonesia (BPS), the United Nations (UN) Comtrade Database, and the International Monetary Fund (IMF). The study employs SWOT analysis, Revealed Comparative Advantage (RCA), Export Product Dynamics (EPD), and the Gravity Model. The results indicate that although national production is substantial, the RCA index remains below 1, reflecting a weak comparative advantage compared to other competitor countries. The Gravity Model confirms that UAE GDP positively influences export volume, whereas geographical distance acts as a significant barrier. This study recommends strengthening quality standardization, especially for compliance with sanitary and halal requirements, optimizing logistics to reduce costs, and implementing premium product differentiation strategies to enhance competitiveness in the UAE market.